126k views
3 votes
Define contrapositive p --> q=?

User Cirrus
by
4.5k points

1 Answer

2 votes

Answer:

~q→~p

Explanation:

The contrapositive of a statement is formed by negating the hypothesis and conclusion of a statement and switching them (the hypothesis becomes the conclusion and vice versa).

With this definition we can conclude that the contrapositive of p→q would be ~q→~p

User Baju
by
4.7k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.